Basic Biology and Applications of Actinobacteria 2018
DOI: 10.5772/intechopen.76802
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Tuberculosis: A Concern and Strategies to Combat

Abstract: Mycobacterium bovis is the main causal agent of bovine tuberculosis that causes zoonotic tuberculosis in humans. The most common routes of transmission of the agent to human are airborne transmission, consumption of unpasteurized milk, direct contact with infected animals or untreated animal products. Conventional diagnostic methods in combination with modern molecular and immunological techniques should be used for early and accurate diagnosis of the disease. Some of the challenges to tackle and eradicate zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
0
20
0
4
Order By: Relevance
“…The working time of workers in slaughterhouses also constitutes the period of exposure to possible infections. The average duration of the workers' exercise was considerable, thus favorable to the risks of contamination by tuberculosis and other zoonoses (4,39). A study in Nigeria found a correlation between the duration of exposure and the degree of risk of contamination by different zoonotic germs (20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The working time of workers in slaughterhouses also constitutes the period of exposure to possible infections. The average duration of the workers' exercise was considerable, thus favorable to the risks of contamination by tuberculosis and other zoonoses (4,39). A study in Nigeria found a correlation between the duration of exposure and the degree of risk of contamination by different zoonotic germs (20).…”
Section: Resultsmentioning
confidence: 99%
“…Infected cattle pose a risk to public health; previous studies have revealed the role of Mycobacterium bovis in the transmission of pulmonary tuberculosis from cattle to humans (39). Tuberculosis screening was not carried out at the level of the slaughterhouse workers interviewed, but certain studies have highlighted the contamination of professionals working in cattle breeding (4,17,40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease is widespread in Central and South America, parts of Asia and Middle East countries. While BTB has been controlled successfully in most developed countries through the application of the test and slaughter schemes, meat inspection at abattoirs and pasteurization of milk, it remains a problem in some developing countries because practice of control programs are either at an early stage or not exist [9,10,11].…”
Section: Introductionmentioning
confidence: 99%